ANALISIS BENTUK GEOMETRI TERHADAP STABILITAS LERENG PADA TAMBANG TERBUKA DARI ASPEK GEOTEKNIK - Lisa Fianti; Munirwansyah Munirwansyah; Halida Yunita (Prodi Magister Teknik Sipil Unsyiah, 2020)
Aceh Province is one of the coal producers, especially Sumber Batu Village in Meurebo District, West Aceh Regency. In the implementation of coal mining, it is necessary to pay attention to the slope stability of open-pit mining to identify and estimate the possibility of landslides. For this reason, the author conducted research in analyzing the geometric shape of the slope stability with the slope variance of modeling the reduction of the existing angle αeks - 10% to the depth of three layers of soil 11 meters. The 1st layer of soil is 1.5 meters, the second layer of soil is 2.5 meters, and the third layer of soil is 7 meters. Slope stability is strongly influenced by the geometric shape of the slope and the strength of soil parameters. To identify the stability of the slope against slope failure, computationally performed using the finite element method with Plaxis software as the reference for the value of FK 1.25, which is considered safe/stable, meaning that collapse rarely occurs. In this research, primary data is used in the form of direct observation in the field, namely taking soil samples to obtain soil data in the form of soil physical properties and soil mechanical properties into soil parameter data, which is tested in the soil laboratory. Secondary data used are map data, boring data, and Sondir data. Soil parameter data were processed using Plaxis software. The results of the slope stability analysis showed that by modeling the geometric shape of the slope (αeks - 10%) on the open slope of a coal mine with a soil depth of 11 meters, the FK value was 3.60. From the results of the FK scores, it shows that the slope of the slope is 3.60 1.25 above the reference value of safe/stable FK. The FK value is 0.2 greater than the FK existing geometry. The conclusion of this study is that geometric shapes play an important role in determining the stability of an open coal pit excavation slope. The smaller the slope angle, the greater the FK value obtained, or the more gentle the slope, the higher the safety value of a slope.